Metode Dakwah Animasi Upin dan Ipin dalam Penanaman Nilai Akhlakul Karimah - Aminah, Siti; Hidayah, Nurul (Darul Yasin Al Sys, 2024)
Islam is a Missionary religion, meaning a religion that always encourages its adherents to always actively carry out missionary activities. Between da'wah and Islam cannot be separated from one another, the methods of da'wah include Bil Lisan, Al-Mujjadi, Bil Hal, Fardiyah, Bit-Tadwin, Mauizhaah Hasanah, Bil Hikmah. Meanwhile, instilling moral values includes 3 points, namely Morals towards Allah, Morals towards humans Morals in religion. This research aims to determine the methods of da'wah and instilling moral values contained in Upin and Ipin animations. The method used in this research is book review, this research is included in the library research category. The data and data sources needed in this research are classified as descriptive qualitative research because the researcher was directly involved in collecting all the data needed. The results of this research obtained several da'wah methods that were applied in Upin and Ipin animations. Choosing a da'wah method that is appropriate to the activities taking place will convey the da'wah maximally according to the objectives. Instilling the values of akhlakul karimah is very influential in children's behavior, children tend to behave in ways that they are used to, therefore instilling the values of akhlakul karimah from an early age is highly recommended so that children have good morals. The Upin and Ipin animation also conveys the message that children should have good character, obey their parents and love their siblings and friends.